2017
DOI: 10.1080/17470218.2016.1223704
|View full text |Cite
|
Sign up to set email alerts
|

Judging the Animacy of Words: The Influence of Typicality and Age of Acquisition in a Semantic Decision Task

Abstract: The age at which members of a semantic category are learned (age of acquisition), the typicality they demonstrate within their corresponding category, and the semantic domain to which they belong (living, non-living) are known to influence the speed and accuracy of lexical/semantic processing. So far, only a few studies have looked at the origin of age of acquisition and its interdependence with typicality and semantic domain within the same experimental design. Twenty adult participants performed an animacy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Based on the literature review, supporting evidence has demonstrated that the access to perceptual, phonological and semantic representations during reading and pictorial processing is where the AoA effect comes from. Specifically, AoA effects have been shown in a range of tasks that require lexical access and articulation not necessitating semantic processing (e.g., Barry et al, 2001; Baumann & Ritt, 2018; Elsherif et al, 2020; Gerhand & Barry, 1998, 1999b; Morrison et al, 1992) and in tasks that necessitate access to semantics but not phonology (for example, Brysbaert et al, 2000; Catling et al, 2021; Catling & Elsherif, 2020; Catling & Johnston, 2006a, 2009; Ellis et al, 2006; Holmes & Ellis, 2006; Johnston & Barry, 2005; Moore et al, 2004; Morrison & Gibbons, 2006; Palmer & Havelka, 2010; Preece, 2015; Räling et al, 2015, 2016, 2017; Stadthagen-Gonzalez et al, 2004, 2009; Vitkovitch & Tyrrell, 1995; but see Bonin et al, 2006; Chalard & Bonin, 2006).…”
Section: Evaluation Of Aoa Theoriesmentioning
confidence: 99%
“…Based on the literature review, supporting evidence has demonstrated that the access to perceptual, phonological and semantic representations during reading and pictorial processing is where the AoA effect comes from. Specifically, AoA effects have been shown in a range of tasks that require lexical access and articulation not necessitating semantic processing (e.g., Barry et al, 2001; Baumann & Ritt, 2018; Elsherif et al, 2020; Gerhand & Barry, 1998, 1999b; Morrison et al, 1992) and in tasks that necessitate access to semantics but not phonology (for example, Brysbaert et al, 2000; Catling et al, 2021; Catling & Elsherif, 2020; Catling & Johnston, 2006a, 2009; Ellis et al, 2006; Holmes & Ellis, 2006; Johnston & Barry, 2005; Moore et al, 2004; Morrison & Gibbons, 2006; Palmer & Havelka, 2010; Preece, 2015; Räling et al, 2015, 2016, 2017; Stadthagen-Gonzalez et al, 2004, 2009; Vitkovitch & Tyrrell, 1995; but see Bonin et al, 2006; Chalard & Bonin, 2006).…”
Section: Evaluation Of Aoa Theoriesmentioning
confidence: 99%
“…Against our hypotheses, word frequency and AoA were not associated with response time. Neuro-QoL items were by design written below a 6th grade reading level, as defined by the Lexile Analyzer, based on word frequency and syntax complexity [ 41 ], which may have restricted the range of word frequencies contained in Neuro-QoL items, as well as AoA, which is strongly correlated with word frequency [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barry et al, 2001;Baumann & Ritt, 2018;Elsherif et al, 2019;Gerhand & Barry, 1998, 1999aMorrison et al, 1992), and in tasks that necessitate access to semantics but not phonology (e.g. Catling et al, 2021;Catling & Johnston, 2006aHolmes et al, 2006;Johnston & Barry, 2005;Moore et al, 2004;Morrison & Gibbons, 2006;Palmer & Havelka, 2010;Preece, 2015;Räling et al, 2015Räling et al, , 2016Räling et al, , 2017Stadthagen-Gonzalez et al, 2004Vitkovitch & Tyrrell, 1995 but see Bonin et al, 2006;).…”
Section: Evaluation Of Aoa Theoriesmentioning
confidence: 99%